Determinants of postharvest losses along smallholder producers maize and sweetpotato value chains: an ordered probit analysis - Shee, Apurba; Mayanja, S.; Simba, E.; Stathers, T.; Bechoff, Aurélie; Bennett, B. (Springer, 2019)
Postharvest loss reduction throughout commodity value chains is an important pathway to food and nutrition security in sub-Saharan Africa. However, lack of understanding of the location and share of the losses and associated factors along the postharvest value chains remains a major challenge to operationalizing postharvest loss mitigation strategies. This paper assesses the determinants of postharvest losses at each postharvest stage of maize and sweetpotato (white fleshed and orange fleshed) value chains for smallholder farmers using our cross-sectional field survey data from two districts in Uganda. An ordered probit model estimation reveals that self-reported perceptions of the level of quantitative postharvest losses at different stages of commodity value chains are influenced by socio-economic factors as well as existing postharvest handling and storage practices. Increased years of education and training received on postharvest management are related to lower perceived levels of postharvest losses at key stages of value chains. Lower perceived postharvest losses are also associated with: at transport to homestead the use of sacks and bicycles as opposed to the use of baskets or transporting by trucks; at drying the use of tarpaulins as opposed to use of plastic sheets; shelling using bare-hands as opposed to beating cobs in sack with sticks; storage in a brick and mortar store as opposed to storing in living room in the house.